Strategic development of the education system is an important factor for a sustainable future - O. Safarov (International Consortium of Education and Culture Research Studies, 2019)
This paper makes analyses of the strategic development of the education system is an important factor for a sustainable future. In this case, research has been conducted both theoretically and methodologically. Therefore, it concluded major points of the research in order to get further disruptive points of the research.